Risk of Abdominal Surgery in Pregnancy Among Women Who Have Undergone Bariatric Surgery. Issue 5 (May 2017) - Stuart, Andrea; Källen, Karin
Abstract : OBJECTIVE: To compare the rates of abdominal surgery during pregnancy among women with previous bariatric surgery (women in the case group) and women with first-trimester body mass index (BMI) greater than 35 and no previous bariatric surgery (women in the control group). METHODS: We conducted a national cohort study, merging data from the Swedish Medical Birth Registry and the Swedish National Patient Registry, comparing women who had bariatric surgery from 1987 to 2011 with women in a control group with first-trimester BMI greater than 35 who had not had bariatric surgery. Primary outcome variables were diagnosis and surgical procedure codes grouped as five outcome categories: 1) intestinal obstruction, 2) gallbladder disease, 3) appendicitis, 4) hernia, and 5) diagnostic laparoscopy or laparotomy without the presence of a diagnosis or surgical code for outcomes in outcome categories 1–4. Odds ratios were computed using multivariate linear regression analysis for each separate pregnancy. For all pregnancies in a given woman, general estimating equations with robust variance estimation were used. Adjustment was made for smoking, year of delivery, maternal age, and previous abdominal surgery. RESULTS: During the first pregnancy after bariatric surgery, the rate of surgery for intestinal obstruction was 1.5% (39/2, 543; 95% confidence interval [CI] 1.1–2.0%) in women in the case group compared with 0.02% (4/21, 909; 95% CI 0.0–0.04%) among women in the control group (adjusted odds ratio [OR] 34.3, 95% CI 11.9–98.7). Similarly, the rate of diagnostic laparoscopy or laparotomy was 1.5% (37/2, 542; 95% CI 1.0–1.9%) among women in the case group compared with 0.1% (18/21, 909; 95% CI 0.0–0.1%) among women in the control group (adjusted OR 11.3, 95% CI 6.9–18.5). CONCLUSION: Bariatric surgery is associated with an increased risk of abdominal surgery during pregnancy. Abstract : Pregnant women with previous bariatric surgery have higher rates of surgery for intestinal obstruction and higher rates of diagnostic laparoscopy and diagnostic laparotomy.